THE REFLECTION OF BRITISH CULTURAL VALUES, SOCIAL INDICATORS, AND LANGUAGE USE IN JOJO MOYES’S WORKS - Tursunova Marxabo Raxmonovna (International Journal of Literature and Language Studies, 2026)
Annotation. This article analyzes the artistic expression of British cultural realities, social markers, and linguistic units in the novels of English writer Jojo Moyes. Specifically, through the analysis of her novels